Harga, Fasilitas dan Kualitas Pelayanan sebagai Penunjang Kepuasan Pengunjung Kolam Renang Tirtayasa Kediri - Gesty Ernestivita; Subagyo Subagyo (POLITEKNIK CAHAYA SURYA, 2020)
The swimming pool is one of the entertainment and vacation facilities that is favourites destination by almost people. This tourism industry is quite developed in Kediri. People who have business in this aeea are competing to improve their facilities and service quality and provide the best prices for visitors in the midst of the intense competition in the swimming pool industry in Kediri, which amounts to dozens. This study aims to analyze the effect of price, facilities and quality both partially and simultaneously on the satisfaction of visitors to the Pool Tirtayasa Kediri. This research is a causality research with a quantitative approach. Pupulation in this research are all visitors of Tirtayasa Kediri Swimming Pool, while the sample is determined by 40 visitors using random sampling. Data were collected using a questionnaire, then analyzed using multiple regression analysis. The results showed the price, facilities and quality of service both partially and simultaneously had a significant effect on visitor satisfaction at the Tirtayasa Swimming Pool in Kediri City. Keywords: Price, Facilities, Service Quality, Visitor Satisfaction